Beyond territorial conceptions of entrepreneurial ecosystems: The dynamic spatiality of knowledge brokering in seed accelerators - Andreas Kuebart; Oliver Ibert (Zeitschrift für Wirtschaftsgeographie, 2019)
In spatial terms, entrepreneurial ecosystems are mostly conceptualized as confined to a specific territory. At the same time, the growing relevance of entrepreneurship in digital fields is underlined. This paper argues that this is contradictory since territorial thinking underestimates the disruptive qualities of new entrepreneurial practices in the digital economy. Using process-based, qualitative case studies on seed accelerators from four regions: Amsterdam, Berlin, Detroit and Hamburg, this study seeks to explore knowledge brokering in entrepreneurship ecosystems and analyzes the corresponding spatial dynamics. Our findings imply that startups in digital fields share knowledge about business models and technologies in a way that is unattainable in classical knowledge clusters. Moreover, we show that most of the observed entrepreneurial practices in seed accelerators crucially rely on extra-regional resources and thus remain only incompletely embedded into the respective regions. Against the background of these results, we suggest that entrepreneurial ecosystems should not be primarily viewed as territorial phenomena. Instead, we suggest that the territorial view on entrepreneurship ecosystems should be complemented with a topological view that foregrounds entrepreneurship as a trans-locally shared practice that is tangent to different regions in different ways.
Keywords: 710; Accelerators; Entrepreneurial Ecosystems; knowledge brokers; Trans-locally shared practices